2015
DOI: 10.1289/ehp.1408887
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Phthalate Exposure and Childhood Growth and Blood Pressure: Evidence from the Spanish INMA-Sabadell Birth Cohort Study

Abstract: BackgroundHuman evidence on the effects of early life phthalate exposure on obesity and cardiovascular disease risks, reported by experimental studies, is limited to a few cross-sectional studies.ObjectivesWe evaluated the associations between prenatal phthalate exposure and childhood growth and blood pressure in a Spanish birth cohort study.MethodsWe assessed exposure using the average of two phthalate metabolite spot-urine concentrations collected from the mothers in the first and third pregnancy trimesters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
5
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(130 citation statements)
references
References 52 publications
6
116
5
3
Order By: Relevance
“…LMW metabolites, including MnBP, MEP, and MiBP, have been associated with childhood obesity (77) (145) (388) (59) (48). Conversely, HMW metabolites have been associated with lower weight gain and lower BMI z-scores in boys but higher BMI in girls (406). …”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…LMW metabolites, including MnBP, MEP, and MiBP, have been associated with childhood obesity (77) (145) (388) (59) (48). Conversely, HMW metabolites have been associated with lower weight gain and lower BMI z-scores in boys but higher BMI in girls (406). …”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…9,10,27 In a small Dutch study utilizing infant cord blood measures of oxidative DEHP metabolites, high cord blood concentrations of one metabolite, MEOHP, were inversely associated with BMI among infant boys. 27 However, phthalate concentrations measured in cord blood are susceptible to contamination 6 and may arise from hospital-based exposures to DEHP at delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Valvi et al 9 reported associations of maternal urinary summed di-(2-ethylhexyl) phthalate (∑DEHP) metabolites with higher body mass index (BMI) in girls but lower BMI in boys in a Spanish birth cohort. In the Mount Sinai Children’s Environmental Health and Disease Prevention Research Center (MSSM), Buckley et al 10 reported associations of maternal urinary ∑DEHP metabolite concentrations with lower percent fat mass in children with no differences in associations between girls and boys, though the study was underpowered to identify sex differences.…”
Section: Introductionmentioning
confidence: 99%
“…As there is uncertainty about the critical trimester of exposure for fetal growth, various studies have averaged contaminant concentrations across pregnancy (e.g. Valvi et al, 2015;Mora et al, 2015). Blood metal concentrations were based on the average of the first and third trimester measures if both were available.…”
Section: Metals Exposurementioning
confidence: 99%